The evaluation of pedestrians’ behavior using M/G/C/C analytical, weighted distance and real distance simulation models - Khalid, Ruzelan; Mohd Nawawi, Mohd Kamal; Kawsar, Luthful A.; A.Ghani, Noraida; Kamil, Anton Abdulbasah; Mustafa, Adli (Springer International Publishing AG, 2015)
M/G/C/C analytical and simulation models have long been used to evaluate the performance of a large and complex topological network. However, such evaluation is only founded on a network’s total arrival rate and its weighted distance. Thus, this paper discusses some concepts and issues in building an M/G/C/C simulation model of a complex geometric system where all its arrival sources and their exact distances to the end of their networks (i.e., corridors) have been taken into consideration in measuring the impacts of various evacuation rates to its throughput, blocking probability, expected service time and expected number of pedestrians. For this purpose, the Dewan Tuanku Syed Putra hall, Universiti Sains Malaysia, Malaysia has been selected as a case study for various evaluations of complex pedestrian flows. These results were analyzed and compared with the results of our analytical and weighted distance simulation models. We then documented the ranges of arrival rates for each of the model where their results exhibited significant discrepancies and suggest ideal rates to best evacuate occupants from the hall. Our model can be utilized by policy makers to recommend suitable actions especially in emergency cases and be modified to build and measure the performance of other real-life complex systems.